Enhancing Smallholder Farmer Access to Prime Markets Through Horizontally & Vertically Linked Collective Production & Marketing - Nkonya, Ephraim M. (2015)
IFPRI-German Embassy Policy Seminar “Achieving Food Security in Africa South of the Sahara through Food Value Chains” on June 8, 2015. Presentation by Ephraim Nkonya, IFPRI.